ANALYSIS OF WORK CLIMATE AND WORK ETHIC ON TEACHER PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT SMA NEGERI 1 PESAM IN BENER MERIAH REGENCY - Masfirah; Mesra B; Sri Rahayu (RADJA PUBLIKA, 2025)
This study investigates the influence of work climate and work ethic on teacher performance, with motivation as an intervening variable, at SMA Negeri 1 Pesam, Bener Meriah Regency. Using a quantitative approach, data was collected from 66 teachers and analyzed using SmartPLS. The results indicate that work climate and work ethic have a positive and significant effect on motivation, and motivation, in turn, positively and significantly affects teacher performance. Work climate also has a direct positive and significant impact on teacher performance. However, work ethic does not have a significant direct effect on teacher performance, and motivation does not mediate the relationship between work climate and teacher performance. The findings suggest that fostering a positive work climate and strengthening work ethic can enhance teacher motivation and ultimately improve teacher performance.